Inclusive Education and Digital Social innovation - Hamburg, Ileana; Bucksch, Sascha (Advances in Social Sciences Research Journal, 2017)
Digital technologies and the internet play an increasingly important role in building innovations with a strong social impact - digital social innovations DSI. Education should support this role and respond at trends as rapid population growth, climate instability, rising poverty, demographic developments. In this paper the role of DSI in inclusive education i.e. in the process of strengthening the capacity of the education systems to reach out to all learners is described. Education for an Inclusive Entrepreneurship i.e. entrepreneurship that contributes to social inclusion to give all people an equal opportunity to start up and operate businesses should be included in strategies of all countries. Particularly target groups in the inclusion process are those who are disadvantage and under-represented in entrepreneurship and self-employment, including youth, women, seniors, ethnic minorities and immigrants, disabled people and many other groups. Examples of projects with authors as active partners and developers of DSI in this context are given.